2019
DOI: 10.1029/2018jd030209
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characterization of Dust Activity in the Central Patagonia Desert (Years 1964–2017)

Abstract: Dust emitted from the southern end of South America (SSA) is transported long distances over the Southern Ocean and deposited over this marine ecosystem. Whether the nutrients released through dissolution have a biogeochemical impact is a question with biological as well as climate implications, yet there is no clear answer. Additionally, the provenance of dust recently found in accumulated snow in East Antarctica is still a matter of debate. The Patagonia desert in SSA is the likely source, but there are no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 122 publications
(183 reference statements)
3
40
0
Order By: Relevance
“…Dust flux records of (a) IND‐25/B5 ice core from central Dronning Maud Land (South Atlantic sector of Antarctica); number of dust days record over southern South America (after Gassó & Torres, 2019) is shown in red color and (b) James Ross Island (JRI) ice core (Antarctica peninsula). Both records show three major stepwise increases during the last century.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dust flux records of (a) IND‐25/B5 ice core from central Dronning Maud Land (South Atlantic sector of Antarctica); number of dust days record over southern South America (after Gassó & Torres, 2019) is shown in red color and (b) James Ross Island (JRI) ice core (Antarctica peninsula). Both records show three major stepwise increases during the last century.…”
Section: Resultsmentioning
confidence: 99%
“…Data source is 20th century ERA reanalysis. The record of number of dust days over southern South America is taken from Gassó and Torres (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dust sources used in this study were selected from those identified by Ginoux et al (), who provided a global map of major dust‐emitting areas. Some of these major dust‐emitting areas in Australia, Southern Africa, and South America are a focus of several regional studies (e.g., Bullard et al, ; Gassó & Torres, ; Vickery et al, ). In the Southern Hemisphere, dust emissions from Australia and South Africa dominantly occur between September and February, while in South America dust is emitted between December and February (Ginoux et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Dominant sources of global dust emissions are found along the so-called "dust belt" that includes arid regions of North Africa, the Arabian Peninsula, Central Asia, and North America (Goudie & Middleton, 2006;Prospero et al, 2002). Although satellite investigations (e.g., Prospero et al, 2002) have shown low dust activity in the Southern Hemisphere, vegetation loss resulting from the combination of climate change and land use could lead to increased dust activity in the region (Bhattachan et al, 2012(Bhattachan et al, , 2013Bhattachan & D'Odorico, 2014;Colazo & Buschiazzo, 2015;Gassó & Torres, 2019;Ginoux et al, 2012;McConnell et al, 2007;Thomas et al, 2005). Moderate Resolution Imaging Spectroradiometer (MODIS)derived dust optical depth data show the existence of dust activity in the Etosha National Park of Namibia and the Makgadikgadi Pans of Botswana in Southern Africa (Ginoux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%